Tidal And seasonal effects on water quality in the Matang Mangrove Forest Reserve, Malaysia - S., Nurhidayu; N. Z, Harun (Canadian Center of Science and Education, 2024)
The Matang Mangrove Forest Reserve (MMFR) in Malaysia, known for its sustainable management, However, the specific relationships between tidal dynamics, seasonal changes, and water quality parameters within MMFR remain understudied. This study investigates the effects of tidal and seasonal fluctuations on water quality by examining seven parameters—Dissolved Oxygen, Salinity, Temperature, Total Dissolved Solids, pH, Turbidity, and Electric Conductivity—alongside river characteristics such as width, depth, and velocity. In-situ measurements were conducted across dry and wet seasons at both high and low tides to capture variability in water quality. The findings indicate that tidal cycles and seasonal changes significantly influence the parameters studied, with distinct patterns observed in relation to tidal conditions. For instance, salinity and turbidity levels were found to increase during high tide, influenced by seawater intrusion, while dissolved oxygen and temperature varied with seasonal rainfall and evaporation. These fluctuations not only reflect the hydrological processes within MMFR but also highlight the sensitivity of water quality to environmental conditions. Understanding these relationships is essential for developing adaptive management strategies that address the challenges posed by climate change and human impacts.